The Monitoring Role of the Governmental council in improving the performance of local Committees: Applied Research in the Wasit Governmental Council - عباس, عبد الرزاق ابراهيم; عباس, قاسم حبوب (Journal of Economics and Administrative Sciences, 2015)
The research aims to identify the elements of performance supervisory good and effective and availability in the Governmental council through examination and analysis of the reality and practice of censorship in this Council through study and evaluate the characteristics of the regulatory effective upon which the Governmental council in the performance of his work and knowledge of their adequacy by comparing the established criteria , and determine the effect of characteristics supervisory the performance standards for the Governmental council, Based search to two assumptions key to check the level of the relationship and the influence of the dimensions of the control in improving the performance using a number of statistical methods, and prove the hypotheses were selected Wasit Provincial Council in order to have the research community, and then choose the members of the council entire totaling (28) members to be sample research.       The research included the current academic years (2003 - 2013) as the basis in Dealing with data and information for the study, The research found a set of  conclusions was the most important , There is a significant effect of the dimensions of the control exercised by the Council to maintain the performance of the local executive bodies , and was influenced by the work of the supervisory board and the quota system and the multi- party system and the lack of coordination of the regulatory agencies of central and local communities in the province.                                                                                                                                                    The study The research recommended , A set of recommendations including: the audit work of the Council should be stripped of quotas and factionalism , and expand the powers of the supervisory board to work to cover all operational units and local departments of federal jurisdiction and work impartially and fairly full and without discrimination in the exercise of its monitoring function